Comparison of hepatoma cell lines and primary human hepatocytes as models to study the development of hepatic steatosis - Huggett, Zoe (2020)
Non-alcoholic fatty liver disease (NAFLD) is a worldwide health burden. The first stage is the accumulation of fat within hepatocytes (hepatic steatosis). Dietary and genetic factors determine steatosis, with particular emphasis on dietary fat, dietary sugars, and patatin-like phospholipase domain containing 3 (PNPLA3) genotype. Primary human hepatocytes (PHH) are currently the gold standard in vitro human model of steatosis but hepatoma cell lines are often used. This thesis aimed to compare the lipid accumulation and metabolism of PHH and hepatoma cell lines, and to develop a system to study the PNPLA3 genotype in relation to nutritional stimuli.